SOURCES OF ENRICHMENT OF THE VOCABULARY OF THE UZBEK AND KORAKALPOK LANGUAGES (Spectrum Journal of Innovation, Reforms and Development, 2023)
The article talks about the enrichment and sources of the lexicon of the Uzbek and Karakalpak languages.